ANÁLISE DE COESÃO EM TEXTOS DE L2: UMA PERSPECTIVA POLIFÔNICA - Fontes, Maria do Carmo Martins (Intercâmbio, 2010)
The present paper aims at analysing how coherence is constructed by means of incorporating the words of others’ in one’s written discourse. The "corpus" consists of two students’ final production in L2 and the class transcription in which their work was built.The theoretical basis for this analysis is supported by the work of Bakhtin (1929) and Halliday and Hasan (1976).